Implications of Applied Linguistics for Language Teaching - Utami, Raden Ayu Tri Ratu (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
As mentioned in Richards & C. Lockhart (1996) cited in Abdullah and Majid (2013: 540) in teaching, teachers who know more about the nature of their teaching can evaluate aspects of teaching that need to be changed. There is some concern among educators in language teaching, English is Broughton is the language that is spoken the most and has been taught as a foreign language in schools all over the world. et al (2003) cited in Tılfarlıoğlu (2020: 405). Therefore, to address the problem, this paper looks at several studies based on Richard C. Jack (2015) on today’s English language instruction helps students learn the language, four skills, and the environment of the teacher. These constructs mean for language teaching. In particular, this study will discuss the implications of AL on issues related to present-day English language instruction facilitates student learning, language and the four skills, and the environment of the teacher. Studies demonstrate that AL is a linguistics-validating tool for theoretical items. It is concluded that every language teacher needs to know how to acquire and develop their competencies, knowledge, and skills in today’s language teaching environment. However, holistically from a cognitive and sociocultural perspective, beliefs about language learning, learning styles, motivation, identity, age, language skills, self-confidence, and anxiety are all topics that are brought up. Language and four skills include teaching and evaluating language systems (grammar, vocabulary, pronunciation, discourse, and pragmatics) and four skills (listening, speaking, reading, and writing). Effective language instruction, on the other hand, is currently viewed as a pedagogical and organizational issue.